The Grants Register 2018 The Complete Guide to Postgraduate Funding Worldwide (Palgrave Macmillan UK, 2018)
The most authoritative and comprehensive guide available to postgraduate and professional funding worldwide.- International coverage of grants in 56 countries, both English and non-English speaking.- Over 1,200 awarding bodies provide information on over 4,900 awards.- Updated annually to ensure accurate information.- Awarding bodies arranged alphabetically with a full list of awards.- Full contact details including telephone, fax, email and websites.- Information on subject areas, level of study, eligibility and value of awards.- Details of application procedures and closing dates.- .